2018
DOI: 10.4103/ijnmr.ijnmr_195_17
|View full text |Cite
|
Sign up to set email alerts
|

The portfolio as a tool for mentoring in nursing students: A scoping review

Abstract: Background:One of the processes leading to education and evaluation promotion in nursing is mentoring. Moreover, using a portfolio leads to promotion of the mentoring process. Due to the importance of mentoring in nursing, its strengthening by the portfolio, the weakness of mentoring in nursing, and the lack of widespread use of portfolio in nursing education, the aim of this study was to determine portfolio content, which can help the mentoring performance.Materials and Methods:The present scoping review stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 36 publications
(49 reference statements)
2
3
0
Order By: Relevance
“…This result was in agreement with (Mollahadi et al, 2018) who studied the portfolio as a tool for mentoring in nursing students, and found that more than half of experts were assistant professors of nursing. Whereas (Hoveyzian et al, 2021) found that half of experts were professors in nursing in addition the current study results assured that the developed portfolio was judged on its content validity by academic experts from different faculties of nursing indicating to the possibility of using it in these faculties .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This result was in agreement with (Mollahadi et al, 2018) who studied the portfolio as a tool for mentoring in nursing students, and found that more than half of experts were assistant professors of nursing. Whereas (Hoveyzian et al, 2021) found that half of experts were professors in nursing in addition the current study results assured that the developed portfolio was judged on its content validity by academic experts from different faculties of nursing indicating to the possibility of using it in these faculties .…”
Section: Discussionsupporting
confidence: 91%
“…This result was in accordance with (Mollahadi et al, 2018) who studied the portfolio as a tool for mentoring in nursing students, and found that majority of nursing students hadn't attended training courses about portfolio.…”
Section: Discussionsupporting
confidence: 89%
“…They also reported they gained new knowledge and constructive skills from clinical learn-ing activities, including through readings, from their peers, mentors and supervisors. Similar literature stated that the ultimate role of a clinical portfolio is to integrate theory and practice in the growth of midwifery students [4,5,18] Participants expressed that the clinical teaching portfolio makes students more responsible for their learning process. Students were able to identify their clinical learning needs and goals and collaborate with their mentors and supervisors to establish appropriate learning and evaluation strategies that will enable them to achieve their learning outcomes.…”
Section: Discussionmentioning
confidence: 95%
“…[3] A clinical teaching portfolio is a practical methodology integrating theory and practice of the growth of midwifery students. [4] In Sub-Saharan Africa, both paper-based portfolios (PBP) and electronic-portfolios (EP) are common, although there is limited evidence for EP. For example, in South Africa a study conducted in Western Cape University revealed that a PBP is recognized as a tool that can help midwifery educators to develop students' analytical and critical thinking.…”
Section: Introductionmentioning
confidence: 99%
“…In continuation, this mentoring portfolio can also aid in helping students decide about their careers and how best they can develop their professional identity. [ 4 6 ] Most of these activities are further strengthened by reflective writing, enabling students to critically analyze their experiences and learning. [ 7 ]…”
Section: S Cope Of P Ortfolio In ...mentioning
confidence: 99%